Penguatan Karakter Gotong Royong melalui Model Pembelajaran Window Shopping - Qorinasari, Dian (YASIN, 2022)
The purpose of this paper is to find out whether the Window Shopping model in science learning can improve the cooperative character of fourth grade students at SDN Polokarto 03. Window shopping is a learning mode based on group work where you broaden your horizons by walking around and looking at other people's work, types This window shopping instills the essence of mutual collaboration and global diversity. In group window shopping, students with different roles work together on group assignments. The teacher is integrated into learning, school activities, enabling students to develop good habits and engage in group cooperation by showing booths that other groups can visit. There are government plans to support the development of global diversity and collaborative character by implementing a six-dimensional self-contained curriculum in the Pancasila student profile. Growth of Global Diversity and Mutual Collaboration. Based on the results of Classroom Action Research that can be carried out in science learning by applying the window shopping learning model to fourth grade students at SDN Polokarto 033 Polokarto District, Sukoharjo Regency for the 2022/2023 Academic Year for two cycles, it can be concluded that the Application of the Window Shopping Learning Model can strengthen the character of Mutual Cooperation in Science Subjects for Grade IV Students at SDN Polokarto 03 for the 2022/2023 Academic Year. Strengthening the character of mutual cooperation is evidenced by a significant increase in pre-cycle and in each cycle. In the pre-cycle, the achievement value of the mutual cooperation character reflection indicator was 53.3%. Then in the first cycle the reflection indicator achievement value was obtained by 64% or an increase of 10.7% and cycle II the reflection indicator achievement value increased to 80% or an increase of 16%.